Birth Outcomes in a Prospective Pregnancy–Birth Cohort Study of Environmental Risk Factors in Kuwait: The TRACER Study - AlSeaidan, Mohammad; Al Wotayan, Rihab; Christophi, Costas A.; Al-Makhseed, Massouma; Abu Awad, Yara; Nassan, Feiby; Ahmed, Ayah; Abraham, Smitha; Boley, Robert Bruce; James-Todd, Tamarra M.; Wright, Rosalind John; Dockery, Douglas W.; et al. (My University, 2016)
Background: Rapid development and westernisation in Kuwait and other Gulf states have been accompanied by rising rates of obesity, diabetes, asthma, and other chronic conditions. Prenatal experiences and exposures may be important targets for intervention. We undertook a prospective pregnancy–birth cohort study in Kuwait, the TRansgenerational Assessment of Children's Environmental Risk (TRACER) Study, to examine prenatal risk factors for early childhood obesity. This article describes the methodology and results of follow-up through birth. Methods: Women were recruited at antenatal clinical visits. Interviewers administered questionnaires during the pregnancy and collected and banked biological samples. Children are being followed up with quarterly maternal interviews, annual anthropometric measurements, and periodic collection of biosamples. Frequencies of birth outcomes (i.e. stillbirth, preterm birth, small and large for gestational age, and macrosomia) were calculated as a function of maternal characteristics and behaviours. Results: Two thousand four hundred seventy-eight women were enrolled, and 2254 women were followed to delivery. Overall, frequencies of stillbirth (0.6%), preterm birth (9.3%), and small for gestational age (7.4%) were comparable to other developed countries, but not strongly associated with maternal characteristics or behaviours. Macrosomia (6.1%) and large for gestational age (23.0%) were higher than expected and positively associated with pre-pregnancy maternal overweight/obesity. Conclusions: A large birth cohort has been established in Kuwait. The collected risk factors and banked biosamples will allow examination of the effects of prenatal exposures on the development of chronic disease in children. Initial results suggest that maternal overweight/obesity before pregnancy should be targeted to prevent macrosomia and its associated sequelae of childhood overweight/obesity.
Keywords: Birth outcomes; Cohort; Kuwait; Obesity; Pregnancy